Embedding Local Wisdom Through Green Transformational Leadership Education for Sustainable Performance - Adda, Harnida Wahyuni; Hasanuddin, Bakri; Natsir, Syahir; Idris, Idris; Kornelius, Yoberth; Mahardiana, Lina; Indriani Ibrahim, Andi; Djufri, Muhammad Rifaldi (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to examine the effect of green transformational leadership education grounded in local wisdom on sustainable performance, with green behavior positioned as a mediating variable among employees at PT Indonesia Morowali Industrial Park (IMIP). Method: An explanatory quantitative research design was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The sample consisted of 100 employees, determined based on the ten-times rule relative to the number of measurement indicators. Data were collected through structured online questionnaires and field observations. The measurement model was evaluated using convergent validity, discriminant validity, and reliability testing, while the structural model was assessed through path coefficients, R², Q², and hypothesis testing using bootstrapping procedures. Results: The findings indicate that green transformational leadership education based on local wisdom has a positive and significant direct effect on sustainable performance (β = 0.519; T = 7.433; p < 0.001) and on green behavior (β = 0.661; T = 11.749; p < 0.001). Green behavior also significantly influences sustainable performance (β = 0.359; T = 4.613; p < 0.001). Furthermore, green behavior partially mediates the relationship between green transformational leadership education and sustainable performance (β = 0.238; T = 4.195; p < 0.001). The model explains 64.5% of the variance in sustainable performance and demonstrates strong predictive relevance (Q² = 0.80). Novelty:This study offers empirical evidence on the behavioral mechanism through which green transformational leadership education embedded in local wisdom enhances sustainable performance. Distinct from existing literature that applies Western-centric frameworks, this research demonstrates that integrating indigenous values such as metapoko-pokofali and mefalo-falo into leadership education strengthens the internalization of pro-environmental behavior. By positioning green behavior as a partial mediating construct, the research provides a contextualized model for strengthening long-term organizational performance in resource-intensive industrial settings.